Optimasi Komposisi Pakan Kuda Dewasa Menggunakan Algoritme Genetika - Rheza Raditya Andrianto; Lailil Muflikhah; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Indonesia is one of a country in the world that has a diversity of livestock population such as cows, goats, sheep, and horses. Over time followed by the modern era, the horse population decreased because of the role of horses in various ways and non-fulfillment of nutrition by the horses feed. In this study tries to implement genetic algorithm to get the composition of feed at a minimal cost but the required nutritional standards remain met so as to maintain the health and stability of the horse breed. The representation used in this study is a real code in which each chromosome initializes the feed ingredients used. The reprodustion method used in this study is extended intermediate crossover combined with reciprocal exchange mutation method, and for the last step elitism selection used as a method for selection. Based on the testing results of this study, the optimal parameters obtained is at 70 population, 250 generation and value combination of crossover rate and mutation rate as 0,5 and 0,5 with the highest fitness 0,18887407184772886. The result obtained in the form of feed composition with a minimum cost based on the nutritional needs of adult horses.